Interaction of new information and existing scheme based on Piaget's theory - M Mubarik; M T Budiarto; R Sulaiman (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aimed at describing the interaction between new received information with the existing scheme. This study used qualitative research methods. Data were obtained through problem-solving test and interview based on the answers on the problem-solving test. The result of data analysis showed there were 4 processes done by subject when getting new information namely 1) assimilation, 2) equilibration, 3) accommodation, and 4) rejection of new information. These results indicate when obtaining new information, a person does not directly incorporate the information into an existing scheme. This is because, someone who already has a scheme tends to maintain the scheme it has. Of course, the interaction of new information with the existing scheme through 1) assimilation, 2) equilibration, 3) accommodation, and 4) rejection of new information is important so that someone canuse the existing scheme if appropriate and change the existing scheme if it is not appropriate.